Relationship between depression, anxiety, stress, and mental healthfatigue among staffs in a healthcare facility in Matu and Daro, Sarawak: a conceptual paper - Mahdi, Abdul Khalid; Yaccob, Yasmin; Adam Assim, Mohamad IbraniShahrimin; Anuar, Faizul Nizar (Human Resource Management Academic Research Society (HRMARS), 2023)
This conceptual paper examines the relationship between factors of depression, anxiety, stress, and mental health’s fatigue among healthcare staffs at the health facility in Matu and Daro, Sarawak. This study employs quantitative techniques and survey involved 145 respondents from five different healthcare facilities. This study applied a descriptive method to show the level of depression, anxiety, stress, and fatigue of the respondents. Levels, prevalence, and significant relationships between the constructs were examined and discussed in relation to the respondents’ mental health. Statistical inferences were induced to gauge the prevalence of mental health based upon depression, anxiety, stress, and fatigue according to the demographic characteristics. In conclusion, this study will contribute the conceptual framework as a guideline for the current study.